Mechanistic interrogation of the asymmetric lithiation-trapping of N-thiopivaloyl azetidine and pyrrolidine. Issue 7 (1st December 2015) - Rayner, Peter J.; Smith, Joshua C.; Denneval, Charline; O'Brien, Peter; Clarke, Paul A.; Horan, Richard A. J.
Abstract : A fundamental study on the mechanism of the s -BuLi/chiral diamine-mediated asymmetric lithiation-trapping of N -thiopivaloyl azetidine and pyrrolidine has revealed that the asymmetric induction is due to a dynamic resolution of configurationally unstable organolithiums. Abstract : A fundamental mechanistic study of the s -BuLi/chiral diamine-mediated lithiation-trapping of N -thiopivaloyl azetidine and pyrrolidine is reported. We show that lithiated thiopivalamides are configurationally unstable at −78 °C. Reaction then proceeds via a dynamic resolution of diastereomeric lithiated intermediates and this accounts for the variable sense and degree of asymmetric induction observed compared to N -Boc heterocycles.